Note on Green Growth for Bhutan - Narain, Urvashi; Toman, Michael; Jiang, Zhiyun (World Bank, Washington, DC, 2014)
Bhutan has recently made significant progress in sustaining economic growth and reducing poverty. Bhutan also has valuable deposits of primary materials including dolomite, lime stone, gypsum, quartzite, stone, and marble, which are useful for fabrication of other materials. Thus, a significant part of Bhutan's current and prospective economic gains come from use of natural resources called, green sectors. The basic message in this note is that Bhutan starts from a solid base in terms of green growth, with additional opportunities for meeting its development goals and overcoming the above mentioned challenges on the basis of its natural resource endowment. However, realizing those opportunities and meeting those challenges will require focusing on the economic contribution from sustainable use of those natural resources, in addition to conservation of the environment. It will also require complementary measures, using the economic surplus (or as economists refer to it, rent) from sustainable natural resource use to help diversify economic activity and address institutional and other constraints. A more comprehensive view of green growth emphasizes sustainable use of natural capital, along with managing environmental risks cost-effectively and in an institutionally sound manner to limit risks to human health and of irreversible degradation of the natural environment. In this context, green growth needs to balance conservation with sustainable economic use of all resources to meet the needs of the present, and maintain opportunities for the future. The note touches upon issues of inclusion where possible but not in a systematic and comprehensive manner. The purpose of the note is to provide food for thought in ongoing discussion of growth strategies for Bhutan, and how green growth ideas may contribute to that discussion.